STATUS GINGIVA SETELAH BERKUMUR REBUSAN DAUN SIRIH HIJAU (Piper betle Linn.) KONSENTRASI 25% PADA PENDERITA GINGIVITIS KATEGORI SEDANG - , ANTINAH LATIF ([Yogyakarta] : Universitas Gadjah Mada, 2013)
ABSTRACT Moderate gingivitis is the most common gingival inflammation caused by dental plaque in or near gingival sulcus. Dental plaque can attack the host defenses due to metabolic activity and stiumlate the inflammation. Moderate gingivitis which is characterized by swollen redness, altering the contour, and bleeding on probing in gums. Commonly gingivitis treatment is decreasing ethiology factor by decreasing bacterials and deposit in oral with antimicrobial mouthwash. Piper betle Linn. leaf has antibacterial activity. The aim of this study was to investigate the effectiveness of gargling with 25% of piper betle Linn. leaf decoction mouthwash in gingival status of moderate gingivitis patients. Subjects consisted of 20 moderate gingivitis patients (aged range 18- 25 years old), divided into 2 groups. Each group consisted of 10 patients who gargled with 25% of Piper betle Linn. leaf decoction mouthwash and 0,1% hexetidine as positive control. Gargling was done for 60 seconds, twice a day in the morning and night for 5 consecutive days. On the first day before and the day after the serial treatment. Gingival Index (GI) was measured. The score of GI was measured before and after gargling. Gingival status data was analyzed by proportion value from before and after gargling, the next test used Mann Whitney (p<0,05). The result of this study showed that the GI score was decreased after treatment. There was no significance difference in GI score of treatment group compare to control group. Thus, gargling 25% of Piper betle Linn. leaf decoction was able to decrease gingivitis and indicate that 25% of Piper betle Linn. leaf decoction has the same effect as hexetidine 0,1%